2023
DOI: 10.2147/cia.s365494
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Cancer: Current Perspectives on Assessment and Monitoring

Abstract: Frailty, an age-related condition of increased vulnerability to acute endogenous or exogenous stressors, is a key barrier to successful treatment of cancer in older people. In this group of patients, assessment of frailty is required before starting a new treatment. According to guidelines, the gold standard to assess frailty in older adults with cancer is geriatric screening followed by geriatric assessment (GA) across essential GA-domains (social status, physical function, nutrition, cognition, emotion, co-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…These patients may also have absolute or relative contraindications for such procedures, including patient refusal, coagulation disorders, receiving anticoagulation treatment, and severe frailty. 41 , 42 This is particularly important since cancer patients are commonly on anticoagulants and/or may be too frail. These factors could make sympathetic block or other interventions more challenging and, if the pain is sympathetically independent, potentially less or not effective.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may also have absolute or relative contraindications for such procedures, including patient refusal, coagulation disorders, receiving anticoagulation treatment, and severe frailty. 41 , 42 This is particularly important since cancer patients are commonly on anticoagulants and/or may be too frail. These factors could make sympathetic block or other interventions more challenging and, if the pain is sympathetically independent, potentially less or not effective.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics are known to contribute negatively to treatment outcomes and may be of particular importance in MM. 22 , 23 For disparities between sexes, it has been shown that the incidence of MM is higher in males than females, but females still undergo higher frequency of autologous stem cell transplantation. 24 As we noted for age, this is likely multifactorial with biologic and behavioral components.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a substantial reduction in muscle mass is predictive of decreased survival in patients undergoing palliative chemotherapy. Furthermore, frailty can increase from 13% to 43% following chemotherapy treatment [ 7 ]. Taken together, these data are relevant given that cachexia, sarcopenia, and frailty may negatively impact the quality of life and treatment outcomes for cancer patients [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%